Velocity differences of throwing taken from different positions in water polo and their correlation with anthropometric characteristics - Yapici, A.; Zeki Özkol, M.; Özçaldiran, B.; Ergün, M. (Serbian Journal of Sports Sciences, 2020)
The primary aim of this study is to determine whether there are correlations between the velocities of throwing taken from various game positions with anthropometric characteristics and the secondary aim is to find out if the throwing velocities vary by the positions. 18 male water polo player participated in the study. The physical characteristics of the players and anthropometric measurements were taken and throwing velocities of overhead, back hand and sweep throw were measured from position 2, 3, 4 and 6. Bushnell sports radar was used for measurement of throwing velocities. Significant positive correlation was found between throwing velocities and shoulder, chest (mesosternale), waist (minimum), forearm girth, arm relaxed and arm flexed and tensed girth, bideltoid and chest (transvers) breadth (p<0.05). Repeated measures of ANOVA results showed that there were significant differences in throwing velocities between different throw forms taken from 4 different positions (p<0.05). In the context of throwing velocities, the main finding of this study was that there were very high differences between throwing velocities taken from position-6 (back hand throw: 50.22 km·h-1, sweep throw: 45.94 km·h-1) and other positions (position-2: 65.94 km·h-1, position-3: 63.83 km·h-1, position-4: 64.78 km·h-1) possibly due to different types of throwing techniques.